Immune responses and gut morphology of Senegalese sole (Solea senegalensis, Kaup 1858) fed monospecies and multispecies probiotics. (17th October 2014) - Batista, S.; Ramos, M.A.; Cunha, S.; Barros, R.; Cristóvão, B.; Rema, P.; Pires, M.A.; Valente, L.M.P.; Ozório, R.O.A.
Abstract The current study aimed to determine the effects of dietary probiotic supplementation on growth, gut morphology and non‐specific immune parameters in Senegalese sole (Solea senegalensis) juveniles during a 1‐month trial. Fish were fed for 1‐month two diets with 1.0 or 4.6 × 106 CFU kg−1) of probiotic A (Bacillus sp., Pediococcus sp., Enterococcus sp. and Lactobacillus sp.) and two diets with 3.5 or 8.6 × 105 CFU kg−1 of probiotic B (Pediococcus acidilactici) and tested against an unsupplemented diet (control). Growth performance, as well as respiratory burst activity, nitric oxide (NO), alternative complement pathway (ACH50), lysozyme and peroxidase activities, was not affected by the dietary treatments. Probiotic supplementation tended to increased growth homogeneity between tanks having diet A1 the best possible alternative to decrease costs associated to size grading. Villous length and number of goblet cells of the anterior intestine did not vary among treatments. Muscle duodenal layer was significantly thicker in fish fed probiotic A compared to probiotic B, when included at the lowest level (A2 versus B2). The current study indicate that the use of the multispecies probiotic at 1.0 × 106 CFU kg−1 might enhance protection against pathogen outbreak and increase nutrient absorption, whereas at the highest concentration could reduced size dispersion among tanks.